Sociopsychological Effects of Labour Migration Abroad on Woman Left Behind - Topçu, Damla; Kalender, İrem Sultan (Gaziantep University, 2026)
Labour migration refers to the movement of individuals who cannot find work in their own countries or are dissatisfied with their jobs to other countries in search of employment. Labour migration has various effects on both migrants and those left behind. This study aims to understand the socio-psychological effects of male labour migration on women. The study was conducted in the Kovancılar district of Elazığ, and the study group consisted of 10 women whose husbands had migrated abroad. Data were collected using the in-depth interview technique of qualitative research. Codes and themes were extracted from the collected data, and thematic analysis was performed The research shows that emigration occurs due to financial difficulties, difficulties in finding work and a lack of professional skills; and that the decision to emigrate is mostly made out of necessity. It was found that women experienced a series of problems, such as increased workload, feelings of insecurity, economic difficulties, deterioration of physical health, and children's illnesses, and that their relationships with their spouses, children, relatives, and social environment were affected to varying degrees, both positively and negatively, During this period, it has been observed that women experience psychological issues such as nervousness/stress, insomnia, anxiety, fear, and mental disorders, and that they employ coping strategies such as patience, humour, and suppressing their emotions to boost their morale and motivation. Women are becoming more visible in the public sphere with their increased responsibilities, but they cannot act independently of patriarchal codes. The research reveals that labour migration abroad plays both a reinforcing and transformative role in gender roles and patriarchal codes.

İşçi göçü, kendi ülkelerinde iş bulamayan veya işlerinden memnun olmayan bireylerin iş aramak için başka ülkelere göç etmesini ifade etmektedir. İşçi göçü, hem göç edenler hem de geride kalanlar üzerinde çeşitli etkilere sahiptir. Bu çalışma, erkek işçi göçünün kadınlar üzerinde yarattığı sosyopsikolojik etkileri anlamayı amaçlamaktadır. Çalışma, Elazığ'ın Kovancılar ilçesinde gerçekleştirilmiş ve çalışma grubu, eşleri yurt dışına göç etmiş 10 kadından oluşmuştur. Veriler, nitel araştırma yönteminin derinlemesine görüşme tekniği kullanılarak toplanmıştır. Toplanan verilerden kodlar ve temalar çıkarılmış ve tematik analiz yapılmıştır. Araştırma, yurt dışına göçün maddi sorunlar, iş bulma güçlüğü ve mesleki beceri eksikliği nedeniyle gerçekleştiğini; göç kararının ise çoğunlukla zorunluluktan alındığını göstermektedir. Kadınların iş yükünün artması, güvensizlik hissi, ekonomik zorluklar, fiziksel sağlığın bozulması ve çocukların hastalıkları gibi bir dizi sorun yaşadıkları ve bu süreçte eşleri, çocukları, akrabaları ve sosyal çevreleriyle olan ilişkilerinin çeşitli derecelerde hem olumlu hem de olumsuz etkilendiği tespit edilmiştir. Bu dönemde kadınların, sinir/stres, uykusuzluk, kaygı, korku, ruhsal bozukluklar gibi psikolojik sorunlar yaşadıkları ve sabır, mizaha vurma ve duygularını göstermemeye çalışma gibi başa çıkma stratejileri kullanarak moral ve motivasyonlarını artırdıkları saptanmıştır. Kadınlar, artan sorumlulukları ile birlikte kamusal alanda daha görünür hale gelmekte ancak ataerkil kodlardan bağımsız hareket edememektedir. Araştırma, yurtdışına işgücü göçünün toplumsal cinsiyet rollerinde ve ataerkil kodlarda hem pekiştirici hem de dönüştürücü bir rol oynadığını ortaya koymaktadır.
Yurt Dışına İşçi Göçünün Geride Kalan Kadınlar Üzerindeki Sosyopsikolojik Etkileri
Keywords: Women's Studies; Kadın Araştırmaları